Role of anterior segment optical coherence tomogram in Descemet's membrane detachment - Kothari, Sonia (Medknow Publications, 2011)
Descemet's membrane detachment (DD) is a rare but serious complication of intraocular surgery. In rare cases where corneal edema is severe and we may not be able to visualize DD on slit-lamp examination, anterior segment optical coherence tomogram (AS-OCT) would be helpful. We describe two patients with DD, highlighting the role of AS-OCT in early diagnosis and management of patients with DD. One of the patients had DD with rolled in edge, which could only be visualized with AS-OCT. In such a situation, AS-OCT can identify the edge of detachment and show the exact position of the rolled edge, which can allow us to plan the surgical strategy to unroll the DD.